2014
DOI: 10.1177/1687814020940096
|View full text |Cite
|
Sign up to set email alerts
|

Study on comprehensive performance evaluation for condensation heat transfer inside the micro-fin tube

Abstract: To develop a comprehensive performance evaluation model of heat transfer tube, the flow condensation heat transfer experiment of R1234yf inside the tube was operated. In this article, the effect of mass flux, condensation temperature, and fin structural parameters on the heat transfer characteristics was studied, and then corrections of heat transfer coefficient and pressure drop predictive effect were checked. Results show that the heat transfer coefficient and pressure drop increase with increasing mass flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Their results suggested that micro-fin tubes could drastically increase heat transfer coefficients. Wei et al [7] developed a comprehensive performance model of heat transfer tubes and experimentally evaluated previous correlations. They found that the heat transfer coefficient and pressure drop both increase with the mass flux and condensation temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that micro-fin tubes could drastically increase heat transfer coefficients. Wei et al [7] developed a comprehensive performance model of heat transfer tubes and experimentally evaluated previous correlations. They found that the heat transfer coefficient and pressure drop both increase with the mass flux and condensation temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Condensers play important roles in different systems, such as air conditioning [1,2], heat pumping [3], refrigeration [4,5], nuclear [6,7], chemical [8,9], etc. Nowadays, condensers with mini/micro-channels are used instead of conventional channels in many industries [10][11][12][13][14][15]. The main reasons are reducing the size of the condensers, refrigeration charge, required space, and overall cost of the process [16].…”
Section: Introductionmentioning
confidence: 99%